Advanced HyperSight imaging for patients with adaptive SBRT of prostate cancer: a longitudinal analysis of tissue demarcation - Schmidt, Ralf; Nguyen, Thien Thanh; Bicu, Alicia Simone; Cvachovec, Paula; Siefert, Victor; Eckl, Miriam; Willam, Marvin; Froelich, Matthias F.; Schönberg, Stefan; Ehmann, Michael; Bürgy, Daniel; Clausen, Sven; et al. (Radiation oncology, 2025)
Cone-beam computed tomography (CBCT)-based adaptive radiotherapy (ART) at the Ethos® linear accelerator (eLinac) allows for daily anatomical and dosimetric adjustments and relies on robust image quality. This study evaluated the longitudinal image quality of the novel HyperSightTM-CBCT (hCBCT) compared to planning CT (pCT), using phantoms and data of prostate cancer patients undergoing adaptive stereotactic body radiotherapy (SBRT). Building on this, the longitudinal contour sharpness of the organs in fractional hCBCT and their usability for ART workflow across fractions was evaluated.
Online veröffentlicht: 16. Oktober 2025
Gesehen am 08.01.2026